Interest rate policy of the Central Bank in the implementation of development-oriented credit relations and economic growth - G. Y. Tsukova (Путеводитель предпринимателя)
The article presents an analysis of interest rate policy of the Central Bank of the Russian Federation in promoting economic growth through the development of credit relations.